(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose. To assess the effect of preterm infant first-month weight gain (FMWG) and feeding type on the development of retinopathy of prematurity (ROP) stages. Material and Methods: We retrospectively reviewed the medical records of 200 preterm infants (gestation age (GA), 24-36 weeks; birth weight (BW), 670-2500 g) who were under supervision during 2015-2018 and underwent ROP screening in due time. The fundus was assessed as per the 2021 International Classification of Retinopathy of Prematurity, third edition. Statistical analyses were performed using SPSS26. Results: The preterm infant FMWG was positively correlated with the GA (r = 0.36, p < 0.05) and the BW (r = 0.36, p < 0.05), and negatively with the stages of ROP (r = -0.38, p < 0.05). The FMWG for infants without ROP was 36% larger (p = 0.000) than for those with ROP. At a FMWG exceeding 367.5 g/month, severe ROP requiring preventive treatment will likely not develop with a sensitivity of 60% and specificity of 78%. The preterm infant FMWG was positively correlated with the feeding type (r = 0.36, p<0.05). Formula-only feeding was more common in preterm infants without ROP than in those with ROP (χ2=4.6, р=0.045). The odds ratio (OR) of no ROP was 2.54 times higher (95% CI, 1.22-5.29) in formula-only fed preterm infants than in mixed-fed preterm infants. Conclusion: The preterm infant FMWG was positively correlated with the GA (r = 0.36, p <0.05) and the BW (r = 0.36, p < 0.05), and negatively correlated with the stages of ROP (r = -0.38, p <0.05). The risk ratio of developing severe ROP requiring preventive treatment was 3.31 higher (95% CI, 1.66-6.58) for preterm infants with a FMWG < 367.5 g/month versus those with a FMWG > 367.5 g/month. The FMWG was positively correlated with the feeding type. The OR of no ROP was 2.54 times higher in formula-only fed preterm infants than in mixed-fed preterm infants.